2006
DOI: 10.1038/sj.bjc.6603067
|View full text |Cite
|
Sign up to set email alerts
|

COX-2-mediated stimulation of the lymphangiogenic factor VEGF-C in human breast cancer

Abstract: Increased expression of COX-2 or VEGF-C has been correlated with progressive disease in certain cancers. Present study utilized several human breast cancer cell lines (MCF-7, T-47D, Hs578T and MDA-MB-231, varying in COX-2 expression) as well as 10 human breast cancer specimens to examine the roles of COX-2 and prostaglandin E (EP) receptors in VEGF-C expression or secretion, and the relationship of COX-2 or VEGF-C expression to lymphangiogenesis. We found a strong correlation between COX-2 mRNA expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
150
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(166 citation statements)
references
References 51 publications
14
150
1
1
Order By: Relevance
“…There are many drugs that may have no direct effect on the process of lymphangiogenesis, but can block tumor-induced lymphangiogenesis by inhibiting pathways responsible for an upregulation of lymphangiogenic factors such as VEGF-C or VEGF-D produced by tumor cells. For example, expression of COX-2 was shown to upregulate VEGF-C or -D in breast cancer 25,34 and lung cancer. 35 In the case of breast cancer, this was primarily due to an activation of prostaglandin receptor EP4, so that both COX-2 inhibitor Celecoxib and the EP4 antagonist ONO-AE3-208 given orally were equally effective in blocking tumor-associated lymphangiogenesis and lymphatic metastasis in a COX-2-expressing mouse breast cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…There are many drugs that may have no direct effect on the process of lymphangiogenesis, but can block tumor-induced lymphangiogenesis by inhibiting pathways responsible for an upregulation of lymphangiogenic factors such as VEGF-C or VEGF-D produced by tumor cells. For example, expression of COX-2 was shown to upregulate VEGF-C or -D in breast cancer 25,34 and lung cancer. 35 In the case of breast cancer, this was primarily due to an activation of prostaglandin receptor EP4, so that both COX-2 inhibitor Celecoxib and the EP4 antagonist ONO-AE3-208 given orally were equally effective in blocking tumor-associated lymphangiogenesis and lymphatic metastasis in a COX-2-expressing mouse breast cancer model.…”
Section: Discussionmentioning
confidence: 99%
“…Chang, et al reported that FGF-2 stimulates the proliferation, migration and tube formation of isolated lymphatic endothelial cells, indicating a direct role in lymphatic vessel growth [38] . In addition, COX-2 demonstrates a positive regulatory role in lymphangiogenesis [39] . Interestingly, all these factors are induced by the EBV-associated oncoprotein, LMP1, in NPC [8,29,30] .…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, little is known about the direct contribution of COX-2 to lymphedema-associated lymphangiogenesis, although positive correlations between COX-2 expression in tumor tissues and lymphangiogenesis and lymph node metastasis have been reported for several human cancers, [28][29][30] as well as the effect of COX-2 inhibition on lymphangiogenesis in a tumor implantation model. 14 In a study utilizing a nonselective COX inhibitor in a mouse tail lymphedema model, ketoprofen treatment normalized the histopathology with increased TNF-a expression and VEGF-C expression.…”
Section: Discussionmentioning
confidence: 99%